Adsorption Characteristics of Oxycellulose in a Competitive Environment with other Substances - Michaela Filipi; Miloslav Milichovský (Adsorption Science & Technology)
A comparison was undertaken of the sorption response of oxycellulose and initial linters, i.e. the short fibres that adhere to cotton seed after ginning, towards Fe 2+ , Ca 2+ and Cd 2+ ions in fibrous slurries. The exceptional adsorption capability of oxycellulose towards metal ions (particularly Cd 2+ ions) was confirmed. However, such adsorption processes are quite complicated and are influenced by the solubility of oxycellulose, its composition and the character of the components released into the supernatant, as well as by the presence of other competitive substances and ions in the aqueous solution. The adsorption capacity of oxycellulose increases with increasing –COOH group content and is distinctly increased by the presence of other competitive ions in the aqueous solution. Most probably, this enhanced adsorption capacity of the support bears some analogy to the superficial aggregation (flocculation) induced by the presence of foreign substances.